Analisis Pengguna Aplikasi Tinder Premium Menggunakan UTAUT 2 - Anggy C, Dita; Safitri, Sisilia Thya; Ngafidin, Khairun Nisa Meiah (MEANS (Media Informasi Analisa dan Sistem), 2023)
The application for making new friends virtually is currently one of the most popular dating applications. One user with another can match each other by swiping to the right. Tinder premium has paid features offered including platinum, gold, and plus. This study aims to find out the most significant variables for premium Tinder application users. This research uses the google form link which is distributed to Tinder users and processed using SmartPLS 4.0.8.4. The results of this study found that the factors that influence the user's intention to frequently use Tinder continuously are tinder platinum, which has the most influence, namely performance expectancy and hedonic motivation. Age, gender, and experience moderation variables do not affect the relationship between exogenous and endogenous variables for the three Tinder premiums (Platinum, Gold, and Plus).